Field scattering localization based on compressed sensing. Issue 11 (9th August 2021) - Tang, Zhiyi; Wu, Yuting; Lin, Peiying; Wei, Lusong; Wu, Zhouyi; Huangfu, Jiangtao
Abstract: In the present study, a regional localization system is proposed based on the variation of the scattering field in ultrawide band (UWB) frequencies. The system uses the UWB antennas to transmit and receive the sweep sparse signal in the measured area. Subsequently, the compressed sensing (CS) algorithm is employed for localization. To increase the positioning accuracy, the randomness of signal distribution should be improved. Different from the previous designs, the scattering obstacles are introduced between the target and the antennas. Through simulation and experiment, a localization system composed of two transmitters and one receiver working at 10–20 GHz is proposed, leveraging the UWB source antennas and grid metal barriers. By complying with the sparse reconstruction algorithm of the CS method, the positioning accuracy of 1.4 mm is obtained in the area of 40 × 40 mm 2 at 40 mm distance. The system is capable of locating in small areas effectively based on simple setup, and potentially applied to human‐computer interaction of wearable devices and other local positioning applications.